The influence of formation water on mass transfer in the coal seam - Trofimov, Vitaly A. (Nexo Revista Científica, 2021)
The construction of a model of mass transfer in coal seams involves consideration of a number of conceptual provisions related to various aspects of this process. First, the theoretical aspects of the phenomena responsible for mass transfer must be considered. Namely, the nature of the fluid flow in a fracturing porous medium is concretized, the role of the stress state of the medium is determined, and the thermodynamic component of the processes is estimated. Secondly, the initial conditions of the state of systems must be determined, which exist in the array before the technogenic interference into it, i.e. before the start of formation development. Thirdly, the corresponding equations must be written out describing the ongoing processes, which actually form the basis of the model. Fourth, it is necessary to develop or adapt methods for solving the corresponding equations in conjunction with the initial and boundary conditions. The obtained solutions should be tested on known analytical solutions to confirm the performance of compiled algorithms for their accuracy and convergence.